FREQUENCY OF CARCINOGENIC SHOCK IN PATIENTS WITH NSTEMI (Journal of Medical & Health Sciences Review, 2025)
Background: Among the various types of acute coronary syndrome, NSTEMI has the most aggravating clinical courses. More severely, the clinical course may present as cardiogenic shock which is associated with a high burden of morbidity and mortality. Identifying the predictors of NSTEMI and the associated frequency of cardiogenic shock is of great value for diagnosis, risk stratification, and management.Objectives: The intention is to assess the incidence of cardiogenic shock among patients presenting with non-ST elevation myocardial infarction (NSTEMI) and how this frequency is modified by age, sex, comorbidities, and specific clinical and biochemical factors.Study Design: A cross-sectional study.Place and duration of study. From 01 December 2024 to 31 May 2025 Cardiology Department Sandeman Provincial Hospital / Bolan Medical College / Hospital, Quetta.Methods: A cross-sectional study was undertaken within a cardiology unit involving a cohort of 100 NSTEMI patients. For each patient, variables including data on clinical history, laboratory results, systolic blood pressure, left ventricular ejection fraction, serum creatinine level, and the presence/absence of diabetes were obtained. The definition of cardiogenic shock was based on standard hemodynamic parameters. The data were analyzed using SPSS version 24.0, with a p-value of